Desenvolvimento de protocolo de condutas e rotinas na terapia nutricional para pacientes com câncer colorretal no Hospital do Câncer - CEONC de Francisco Beltrão - Paraná - Weissheimer, Angela Cristina (Universidade do Vale do Rio dos Sinos, 2016)
This work aims to develop a protocol for conducts and nutritional therapy routines for patients with diagnosis of rectal colon cancer (CCR) in the Francisco Beltrão Cancer Hospital, seeking to improve the care, evaluation and nutritional follow-up of patients, acting in Preventive and immediate way in the necessary nutritional intervention and in an individualized way. The use of this protocol turns to nutritionists, to be applied specifically to patients with colorectal cancer. Such use makes it indispensable to understand the methods and techniques determined here, the accuracy of filling all data and conduct so that this monitoring allows a thorough evaluation of the nutritional evolution of the patient. The effective use of the standardization protocol for nutritional therapy routines and routines is the beginning of a differentiated format in patient care, seeking agility, confidence and security in the information provided, guaranteeing to the multidisciplinary team current data regarding the patient's nutritional status for Performance in their respective areas. Its implementation will bring greater individuality in the attention to the needs of each patient and continuous follow-up, seeking to meet the current and individual needs of each patient during the entire treatment, from diagnosis to hospital discharge.
Keywords: Protocolo; Câncer cólon retal; Avaliação; Protocol; Rectal colon cancer; Evaluation; ACCNPQ::Ciências da Saúde::Nutrição